Digital interventions in adult mental healthcare settings: recent evidence and future directions. Issue 4 (July 2020) - Dülsen, Patrick; Bendig, Eileen; Küchler, Ann-Marie; Christensen, Helen; Baumeister, Harald
Abstract : Purpose of review: Internet and mobile-based interventions (IMI) can be used as online delivered forms of psychotherapeutic mental health treatments. These interventions can be an effective as well as time and cost-efficient treatment with the potential to scale up mental healthcare. In this review, we map implementation possibilities into routine mental healthcare settings and provide the most recent evidence. Recent findings: Fourteen articles on digital mental healthcare approaches published in the last 18 months were included. Despite the limited number, the studies provide evidence for the effectiveness of IMI in treating inpatients and outpatients with various disorders in different mental healthcare settings. IMI were investigated as stand-alone interventions, in combination with other treatment forms (blended-care), or as aftercare. Summary: Although there is encouraging evidence for the effectiveness of IMI in mental healthcare settings, several limitations have to be considered. The small number of studies conducted within the healthcare system, especially with inpatient samples, calls for more collaboration between researchers and clinical practitioners to unravel barriers and develop efficient protocols for the integration into routine care. Nonetheless, IMI are a promising tool for the endeavour of closing the treatment gap and should, therefore, be further explored in varying settings. Abstract : Supplemental Digital Content is available in the text